COMPREHENSIVE ANALYSIS OF LABORATORY TESTING UTILIZATION IN EMERGENCY MEDICINE: EVALUATING APPROPRIATENESS, COST-EFFECTIVENESS, AND CLINICAL IMPACT. - ABDALLAH HADY NASER ALLSLOOM, RAYAN SADAAN ALYAMYI, YAHYA SALEH YAHYA AL YAMI, MANSOUR HADI ALI AL-SALLOUM, ALI MOHAMMAD AL GAITHAN, MOHAMMED ATEEQ HUSSEIN AL YAMI, HUSSAIN ATEEQ HUSSAIN AL YAMI, HUSSAIN HADI ALI LSLOUM (Chelonian Research Foundation, 2022)
The choice of laboratory testing by emergency medicine not only impacts the process of patient diagnosis but also helps manage patients and outcomes. This paper intends to conduct a thorough investigation of laboratory testing in the emergency medicine area, including its relevance, cost-effectiveness, and effects on clinical service. This is mainly done using existing literature along with the analysis of data. Factors that lead to laboratory test utilization are investigated here, too, such as clinical indications, which include ordering patterns, test selection, and effects on the patient’s health. The results underpin the necessity of laboratory testing reformation and the improvement of the quality of patient care, the cost-effectiveness of medical care, and the intelligent usage of healthcare resources in emerging departments. Keywords: lab assessment and emergency treatment, relevant tests, efficacy and cost, clinical consequences.